SOCIAL ORDERS AND POLITICAL ANALYSIS OF REGIONAL PROCESSES - A. D. Voskressenski (Сравнительная политика, 2015)
Abstract: Contemporary Political Science deals mainly with three major research fields (typology of social order within countries, existing and emerging regional identity and world order in international system), which are studied separately. This division is a product of the traditional, West-centric theories. The current article building upon achievements of the Russian school of Asian studies and new reality of the West and East proposes framework for complex approach towards political reality with due account of interdependence between global, regional and national levels.